Hematopoietic Stem Cell Transplantation for Severe Combined Immunodeficiency - Hönig, M.; Schulz, A.; Friedrich, W. (Klinische Pädiatrie, 2011)
Severe combined immunodeficiency (SCID) is a heterogeneous group of congenital diseases characterized by their presentation with life threatening infections in the first months of life. The clinical presentation and the therapeutic outcome is influenced by multiple factors: the genetic defect, infectious complications, the presence of maternal T cells the development of Omenn syndrome, as well as non-immunological signs and symptoms of the disease. Hematopoietic stem cell transplantation (HSCT) to date is the only established curative option and allows long-term cure of the disease. Therapeutic objectives of HSCT in SCID clearly differ from those in malignant or hematological disease. Disease specific aspects and their influence on the therapeutic strategy in SCID will be discussed in this review.
Keywords: SCID; transplantation; conditioning; matched donor; mismatched donor; T cell reconstitution